Epidemiology of bone tumors in Lebanon: a retrospective study from 2000 to 2022 at a tertiary center - Mohammad Daher; Ziad Zalaquett; Elio Mekhael; Marven Aoun; Ralph Chalhoub; Majd Abdo; Marc Aoude; Sami Abi Farraj; Ali Ghoul; Jean Tarchichi; Joe Rassi; Amer Sebaaly; et al. (Future Science OA)
Aim: Bone tumors are rare and have an uneven geographic distribution. Methods: 730 patients diagnosed with bone tumors were included in this retrospective analysis. Results: With a 64% rate of malignancy, the most common tumors were metastasis (40%) mostly in the axial skeleton, Osteosarcoma (9%) mostly in the femur, Osteochondroma (8%) mostly in the femur, giant cell tumors (7%) mostly in the knee, and Ewing's sarcoma (6%) mostly in the axial skeleton. Conclusion: Even though a some of the tumors have a predilection for certain localizations in the human body, they may differ in the middle-eastern population. One must also pay attention to the higher rates of malignancies as compared with other cohorts.